Trypanosoma congolense Infections: Induced Nitric Oxide Inhibits Parasite Growth In Vivo - Wenfa Lu; Guojian Wei; Wanling Pan; Henry Tabel (Journal of Parasitology Research)
Wild-type (WT) C57BL/6 mice infected intraperitoneally with 5×106 Trypanosoma congolense survive for more than 30 days. C57BL/6 mice deficient in inducible nitric oxide synthase (iNOS−/−) and infected with 103 or 5×106 parasites do not control the parasitemia and survive for only 14±7 or 6.8±0.1 days, respectively. Bloodstream trypanosomes of iNOS−/− mice infected with 5×106  T. congolense had a significantly higher ratio of organisms in the S+G2+M phases of the cell cycle than trypanosomes in WT mice. We have reported that IgM anti-VSG-mediated phagocytosis of T. congolense by macrophages inhibits nitric oxide (NO) synthesis via CR3 (CD11b/CD18). Here, we show that during the first parasitemia, but not at later stages of infection, T. congolense-infected CD11b−/− mice produce more NO and have a significantly lower parasitemia than infected WT mice. We conclude that induced NO contributes to the control of parasitemia by inhibiting the growth of the trypanosomes.